FTIR and Raman studies of manganese phosphate glasses - Budi, Agus Setyo; Nasbey, Hadi; Sugihartono, Iwan (Universitas Riau, 2024)
Raman and infrared (IR) spectra of xMn2O3(1-x)P2O5 glasses (x = 5 mol% – 25 mol%) are reported. The spectral shift is related to changes in the coordination of the neodymium ion. The changes observed are consistent with an elongation of P–O- terminal and P–O–P bridging bonds in the PO4 tetrahedra.